2011
DOI: 10.1038/gt.2011.143
|View full text |Cite
|
Sign up to set email alerts
|

Novel random peptide libraries displayed on AAV serotype 9 for selection of endothelial cell-directed gene transfer vectors

Abstract: We have demonstrated the potential of random peptide libraries displayed on adeno-associated virus (AAV)2 to select for AAV2 vectors with improved efficiency for cell type-directed gene transfer. AAV9, however, may have advantages over AAV2 because of a lower prevalence of neutralizing antibodies in humans and more efficient gene transfer in vivo. Here we provide evidence that random peptide libraries can be displayed on AAV9 and can be utilized to select for AAV9 capsids redirected to the cell type of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 50 publications
4
101
1
1
Order By: Relevance
“…Furthermore, the anti-AAV9 antibody ADK9 did not neutralize the variants. 31 These results indicate that it may be possible to simultaneously select for two independent properties: antibody resistance and maintenance of existing or engineering of novel tropism.…”
Section: In Vitro Selection and Evolutionmentioning
confidence: 95%
See 3 more Smart Citations
“…Furthermore, the anti-AAV9 antibody ADK9 did not neutralize the variants. 31 These results indicate that it may be possible to simultaneously select for two independent properties: antibody resistance and maintenance of existing or engineering of novel tropism.…”
Section: In Vitro Selection and Evolutionmentioning
confidence: 95%
“…In addition, a chimeric variant isolated by Yang et al 29 from an in vivo selection to identify a muscle-targeting variant (described in more detail below) exhibited a similar level of in vitro resistance to intravenous immunoglobulin as compared to AAV8, and a higher level of resistance compared to AAV2. Finally, Varadi et al 31 demonstrated that random peptide insertions can alter AAV immunoreactivity, as AAV9-SLRSPPS and AAV9-RDVRAVS vectors exhibited enhanced in vitro transduction in the presence of intravenous immunoglobulin compared with wild-type AAV2 and AAV9. Furthermore, the anti-AAV9 antibody ADK9 did not neutralize the variants.…”
Section: In Vitro Selection and Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…by error-prone PCR, or they comprise pools of random peptides that are displayed on the AAV capsid in certain relevant positions. [15][16][17][18][19] In theory, such libraries allow to select for particles with the ability to target any unique structure on the cell surface. 15,[20][21][22] The screening of random AAV display peptide libraries is the only approach to select peptides directly within the structural constraints of the assembled AAV capsid.…”
Section: Technical Issues: Generating Targeted Vectors From Random Aamentioning
confidence: 99%